Parental Investment Under Predation Threat in Incubating Common Eiders (Somateria mollissima): A Hormonal Perspective - Mohring, Bertille; Angelier, Frédéric; Jaatinen, Kim; Parenteau, Charline; Öst, Markus (Frontiers in Ecology and Evolution, 2021)
Predation risk affects the costs and benefits of prey life-history decisions. Predation threat is often higher during reproduction, especially in conspicuous colonial breeders. Therefore, predation may increase the survival cost of breeding, and reduce parental investment. The impact of predation risk on avian parental investment decisions may be hormonally mediated by prolactin and corticosterone, making them ideal tools for studying the trade-offs involved. Prolactin is thought to promote parental care and commitment in birds. Corticosterone is involved in allostasis and may either mediate reduced parental investment (corticosterone-fitness hypothesis), or promote parental investment through a reallocation of resources (corticosterone-adaptation hypothesis). Here, we used these hormonal proxies of incubation commitment to examine the impact of predation risk on reproduction in common eiders (Somateria mollissima) breeding in the Baltic Sea, and subject to high but variable predation pressure on adults and nests. We investigated baseline hormonal levels and hatching success as a function of individual quality attributes (breeding experience, female and duckling body condition), reproductive investment (clutch weight), and predation risk. We expected individuals nesting in riskier environments to reduce their parental investment in incubation, reflected in lower baseline prolactin levels and either higher (corticosterone-fitness hypothesis) or lower (corticosterone-adaptation hypothesis) baseline corticosterone levels. Contrary to our predictions, prolactin levels showed a positive correlation with nest predation risk. The unexpected positive relationship could result from the selective disappearance of low-quality females (presumably having low prolactin levels) from risky sites. Supporting this notion, female body condition and hatching success were positively correlated with predation risk on females, and baseline prolactin concentrations were positively correlated with duckling body condition, a proxy of maternal quality. In line with the corticosterone-adaptation hypothesis, baseline corticosterone levels increased with reproductive investment, and were negatively associated with nest predation risk. Hatching success was lower on islands where nest predation risk was higher, consistent with the idea of reduced reproductive investment under increased threat. Long-term individual-based studies are now needed to distinguish selection processes occurring at the population scale from individually plastic parental investment in relation to individual quality and variable predation risk.